2021
DOI: 10.35440/hutfd.1001970
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Role of C-Reactive Protein/Albumin Ratio in Patients with Critical COVID-19 Patients

Abstract: Amaç: COVID-19 hastalarının yönetimindeki önemli gelişmelere rağmen, tedaviyi yönlendirecek, hastalık şiddetini öngören belirteçlere ihtiyaç vardır. Biz de bu çalışmada; C-reaktif protein/Albumin (CRP/Alb) oranının hastalık şiddeti ile ilişkisini ve yoğun bakım ihtiyacını tahmin etmedeki rolünü değerlendirmeyi amaçladık. Materyal ve metod: Ocak 2021 ile Haziran 2021 tarihleri arasında hastanemizde COVID-19 enfeksiyonu nedeniyle takip edilen hastaların klinik bulguları, laboratuar sonuçları ve akciğer bilgisaya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Graciano et al (14) reported an approximately 70% decrease in admissions to intensive care units during the pandemic. COVID-19 primarily affects the upper respiratory tract, explaining the significant increase in the number of nose and throat cultures during the pandemic (15,16). The significant decrease in the number of ear cultures during the pandemic was a result of avoidance of ear infection risks (e.g., swimming pools).…”
Section: Discussionmentioning
confidence: 99%
“…Graciano et al (14) reported an approximately 70% decrease in admissions to intensive care units during the pandemic. COVID-19 primarily affects the upper respiratory tract, explaining the significant increase in the number of nose and throat cultures during the pandemic (15,16). The significant decrease in the number of ear cultures during the pandemic was a result of avoidance of ear infection risks (e.g., swimming pools).…”
Section: Discussionmentioning
confidence: 99%